Stories from Abakwa - Nyamnjoh, Francis B., 1961- (Book collections on Project MUSE., 2007)
Childhood and growing up in Mimboland, Cameroon are infused with fascinating stories and adventures. Discover life in Abakwa with Tom and his friend, as they are chased through an orchard for secretly harvesting avocadoes and mangoes. Smile as Mathias Chi's overloaded canoe almost loses balance. Shiver as Roland runs through the dark streets and bleeding corridors of Mvog Mvog. And cry when Big Brother discovers how his siblings suffered when he was away at school. What happens to Esther when she finds the courage to make an announcement at the Abakwa Mountain Foot Radio Station about her husband's disappearance? Will Prudencia and Collette kill or give life? How does Prisca Lum deal with her dwarf husband? Some characters will remind you of people you know - or even of yourself. Drum beats and church bells, thunder and lightning, princes and princesses, visions and deceptions fill the pages. Discover your favorite stories waiting to be told and retold, again and again.